Foraging pattern of major pollinator fauna of sunflower: Foraging pattern of major pollinator fauna of sunflower - K M SRINIVAS REDDY,; Y G SHADAKSHARI,; S D NEHRU,; K KARUNA,; M S UMA, (Journal of Oilseeds Research, 2020)
The activity of pollen and nectar foragers were assessed in sunflower hybrid KBSH 53. Their foraging activitycommenced from 6.00 hrs and continued till 18.00 hrs. The major Apis bee pollinators included Apis dorsata, A.cerana indica and A. florea and non Apis bees included Xylocopa pubescens F., Xylocopa fenestrate F., Tetragonula iridipennis S. and Ceratina binghami C. This study carried out for four consecutive years revealed that A. dorsata foraged for maximum time of 11 hours (7.01-8.00 hrs to 17.00-18.00 hrs) compared to other foragers. A. cerana and A. florae were active for only 10 hour (8.01-9.00 to 17.01-18.00 hours) and Tetragonula irridipennis for 5 hrs (13.01- 14.00 to 17.00-18.00 hrs).